MELIHAT TINDAK PIDANA PENYELUNDUPAN (SMUGGLING OF MIGRANTS) PMI NON PROSEDURAL SEBAGAI SUATU KEJAHATAN YANG BERSIFAT VICTIMLESS - Bakhtiar, Masdar; Hanuun, Khoirunnisa Dhiyaa (Polteknik Imigrasi, 2024)
The warm case of news about PMI-NP, which has recently been carried out by many Indonesians, has become a complex problem. In media reports, many said that PMI-NPs who were thwarted by their attempts to cross were called